2009
DOI: 10.2175/106143009x407258
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosol in Composting Facilities: Occupational Health Risk Assessment

Abstract: This research found evidence of an association between occupational exposure to bioaerosols in composting plants and health outcome occurrence in exposed workers. An occupational exposure assessment in six composting plants was performed to better characterize personal exposure levels and evaluate associated health risk in workers. Sampling results showed large ranges of concentrations of dust, bacteria, molds, and endotoxin in ambient air and in personal samples, both when driving a front-end loader and when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…Bioaerosols occur naturally in ambient air at highly variable concentrations, with mean and median background concentrations ranging from 1 to 100,000 colony-forming units per cubic meter (cfu/m 3 ) for bacteria and fungi (Clark et al, 1983;Coccia et al, 2010;Crook et al, 2008;Deacon et al, 2009;Drew et al, 2007;Fischer et al, 2000, Herr et al, 2003b, Nadal et al, 2009Nikaeen et al, 2009;Reinthaler et al, 1999Reinthaler et al, , 2004Schlosser et al, 2009;Stagg et al, 2010;Swan et al, 2003;van Kampen et al, 2012;Williams et al, 2013).…”
Section: Acceptable Limits For Bioaerosolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bioaerosols occur naturally in ambient air at highly variable concentrations, with mean and median background concentrations ranging from 1 to 100,000 colony-forming units per cubic meter (cfu/m 3 ) for bacteria and fungi (Clark et al, 1983;Coccia et al, 2010;Crook et al, 2008;Deacon et al, 2009;Drew et al, 2007;Fischer et al, 2000, Herr et al, 2003b, Nadal et al, 2009Nikaeen et al, 2009;Reinthaler et al, 1999Reinthaler et al, , 2004Schlosser et al, 2009;Stagg et al, 2010;Swan et al, 2003;van Kampen et al, 2012;Williams et al, 2013).…”
Section: Acceptable Limits For Bioaerosolsmentioning
confidence: 99%
“…• Variations in sampled concentration with season (fungal concentrations were overall greater in summer than winter; Schlosser et al, 2009). …”
Section: Exposure Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly we did not account for variations in seasonality, as this study was designed to look at spatial and not temporal variability in respiratory admissions. While a handful of studies have reported that there is some seasonal variation in bioaerosol concentrations with elevations in the summer and winter months (Neilsen et al 1997;Recer et al 2001;Schlosser et al 2009), the evidence base is limited and the relationship between bioaerosol emissions from composting facilities and season is not well understood. Future work is needed to improve exposure estimates.…”
Section: Discussionmentioning
confidence: 99%